Genome Sequence of Amycolatopsis sp. Strain ATCC 39116, a Plant Biomass-Degrading Actinomycete - Davis, Jennifer R. (American Society for Microbiology, 2012)
We announce the availability of a high-quality draft of the genome sequence of Amycolatopsis sp. strain 39116, one of few bacterial species that are known to consume the lignin component of plant biomass. This genome sequence will further ongoing efforts to use microorganisms for the conversion of plant biomass into fuels and high-value chemicals.